Breast cancer knowledge among students of high schools from Lublin region - Jankowska, Paula; Jankowski, Krzysztof; Mizerski, Grzegorz; Rudnicka-Drożak, Ewa (Journal of Education, Health and Sport, 2018)
Introduction Breast cancer, with an estimated 1.67 million new cases diagnosed in 2012 (25% of all cancers), is the second most common neoplasm worldwide. It is also the most frequent proliferative process among women.Objective Evaluation of the level of students’ knowledge concerning risk factors and prophylaxis of breast cancer.Material and methodsThe study was conducted among randomly selected students of high schools from Lubelskie region between April and June 2017. Participation in the study was voluntary and anonymous. The study group consisted of 137 students. The study used the method of a diagnostic survey using a questionnaire constructed by the authors. The obtained results were statistically analyzed using the STATISTICA 13 program. The significance of intergroup differences was verified with Pearson chi-square test. ResultsThe vast majority of students indicated the following main risk factors of breast cancer: family history, genetic predispositions, smoking and advanced age. In the respondents opinion, palpable tumor, changes in the size or shape of the breast and enlargement of axillar lymph nodes were the main symptoms of breast cancer. The Internet was indicated as the main source of breast cancer knowledge.ConclusionsInterviewed students showed relatively low level of knowledge concerning problem of breast cancer risk factors. Young people use Internet as a main source of information about breast cancer and its prophylaxis. According to the results, it is necessary to mobilize health professionals, to promote rules for the prevention of breast cancer among young women. There is a need of new, wide, persuasive social campaigns from the area of breast cancer prevention.